Interorganizational Groups: Origins, Structure, and Outcomes - Schopler, Janice H. (Academy of Management Review, 1987)
Interorganizational groups are important ways of linking organizations, yet little is known about the relative costs and benefits of different types of groups. A conceptual framework, based on a macro perspective and addressing some micro issues, is used to predict group operation and outcomes under four conditions.